2022
DOI: 10.1002/adma.202108848
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa‐Like Conformal Hydrogel Coating for Aqueous Lubrication

Abstract: Mucosa is a protective and lubricating barrier in biological tissue, which has a great clinical inspiration because of its slippery, soft, and hydrophilic surface. However, mimicking mucosal traits on complex surface remains an enormous challenge. Herein, a novel approach to create mucosa‐like conformal hydrogel coating is developed. A thin conformal hydrogel layer mimicking the epithelial layer is obtained by first absorbing micelles, followed by forming covalent interlinks with the polymer substrate via inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…These results showed that the tissue adhesion of Glue 3 after NIR light irradiation was stronger than that of Glue 1, which was because that UCNPs within the glues could efficiently convert NIR light into UV light as an internally secondary light source to induce the imine crosslinking reaction on tissue interface. Compared to previous tissue adhesives, [22,[49][50][51] the bio-glues developed in the current study could work well for the adhesion strength and wound healing in small animals (i.e., rats, rabbits) and even larger animals (i.e., pigs, dogs, monkeys). Finally, the wet adhesion properties of the glues to bind skin tissue were further investigated.…”
Section: Adhesion Capability Of Bio-gluesmentioning
confidence: 92%
“…These results showed that the tissue adhesion of Glue 3 after NIR light irradiation was stronger than that of Glue 1, which was because that UCNPs within the glues could efficiently convert NIR light into UV light as an internally secondary light source to induce the imine crosslinking reaction on tissue interface. Compared to previous tissue adhesives, [22,[49][50][51] the bio-glues developed in the current study could work well for the adhesion strength and wound healing in small animals (i.e., rats, rabbits) and even larger animals (i.e., pigs, dogs, monkeys). Finally, the wet adhesion properties of the glues to bind skin tissue were further investigated.…”
Section: Adhesion Capability Of Bio-gluesmentioning
confidence: 92%
“…The dynamic behaviors enabled the tissue-like properties of programmability, anisotropy, and trainability. Bai et al (2022) developed a mucosa-like conformal hydrogel coating. By first absorbing micelles, then forming covalent interlinks with polymer substrate through interface-initiated hydrogel polymerization, a thin hydrogel layer similar to the epithelial layer was achieved.…”
Section: Need For Advanced Tissue-like Materialsmentioning
confidence: 99%
“…There is less advancement in the lubrication coating on intravascular medical devices, but some new technology about lubrication coating emerged recently ( 22 ). A novel approach to create mucosa-like conformal hydrogel coating was developed.…”
Section: The Progress In Lubrication Coating Technologymentioning
confidence: 99%